Effects of interferonotherapy and Lamivudine monotherapy of HBV infection in a patient with chronic myelogenous leukemia. Case report - Karczmarek-Borowska, Bożena; Fota-Markowska, Hanna; Lis-Tonder, Joanna; Modrzewska, Roma (Contemporary Oncology/Współczesna Onkologia, 2004)
HBV infection brings about some serious prognostic and therapeutic problems especially in the case of complicated hematopoietic, lymphatic and reticuloendothelial system malignancies. In this paper, the effect of interferonotherapy and Lamivudine monotherapy of HBV infection of a patient with chronic myelogenous leukemia (CML) is presented. The 30-year-old patient with coexisting HBV infection, chronic hepatitis B and chronic myelogenous leukemia (CML Ph), treated with chemotherapy, then unsuccessful bone marrow transplantations was assigned to INF-therapy (doses of 2-5 mln three times a week, based on serological HBV markers profile: HBsAg(+), HBeAg(+), anti-HBc IgM(+) and viremia 6418 pg/ml (Digene Hybrid Capture System - Murex). Viremia decreased to 3 808 pg/ml after 4 months and to 2 907 pg/ml after 7 months of therapy, whereas HBsAg, HBeAg and anti-HBcIgM were present. After 11 months of therapy serologic HBV markers were still present, but the HBV-DNA serum level increased to 6 209 pg/ml. In view of these data, a decision of Lamivudine administration with a daily dose of 150 mg was made. After three months of this therapy, an undetectable serum HBV-DNA level and a normal serum transaminase activity without serum HBsAg clearance were found. Then, with the antiviral therapy with the same dose of Lamivudine continued, BMT procedure was performed. The presented case report confirms the role of active immunization of patients with hematopoietic system disorders.